Non-adherence to anti-retroviral therapy among HIV infected adults in Mon State of Myanmar - Win Lei Aye; Apa Puckpinyo; Karl Peltzer (BMC, 2017)
Abstract Background The provision of Anti-Retroviral Therapy (ART) was started in Myanmar in 2005 in collaboration with the National AIDS Program and the private sector. Successful clinical management of HIV-infected patients is subject to optimal adherence. The aim of the study was to determine the prevalence of adherence to ART and identify factors associated with non-adherence to ART among HIV infected adults registered in a private sector setting in Mon State, Myanmar. Methods This cross-sectional study was conducted with adults living with HIV receiving ART at an HIV outpatient clinic between April and May 2016. A total of three hundred People Living with HIV(PLHIV) were interviewed using a pretested and structured questionnaire. The 30 days Visual Analog Scale (VAS) adherence instrument was used to assess the level of adherence. Multivariable logistic regression analysis was used to determine factors associated with non-adherence to ART. Results Among 300 patients (male 37.7% and female 62.3%, with a mean age of 41.3 years, standard deviation 8.7), 84% reported ≥95% adherence to ART in the past month. Among 16% of those reporting non-adherence, major reasons for skipping the medication were being busy (23%), being away from home (17.7%) and being forgetful (12.3%). In multivariable logistic rgeression, low behavioural skills on ART adherence (OR = 0.31, 95% CI: 0.10-0.94), tobacco use (OR = 3.22, 95% CI:1.28-8.12), having disclosed their HIV status (OR = 0.07, 95% CI: 0.01-0.69), having a partner who was not on ART (OR = 4.25, 95% CI: 1.70-10.64) and among men, having erectile dysfunction (OR = 15.14, 95% CI: 1.41-162.66) were significant associated with ART non-adherence. Conclusion Non-adherence to ART was associated with individual moderating factors and behavioral skills. Priority measures such as addressing risk behaviour and behavioural change communication tailored to individual patients' lifestyles requires comprehensive interventions to improve adherence.